Urban poverty in Bangladesh improving slum life /produced by the Information Office, Asina Development Bank ; director/videographer, Steven Groffiths. - Griffiths, Steven; Salamon, Robert (Asian Development Bank, 1996)
In Dinajpur, an innovative slum improvement project is demonstrating a way forward. the proect is providing critical social and physical infrastructure, and skills training for community residents. The project may serve as a model for others, allowing slum dwellers to lead healthier, happier and more productive lives.